2011
DOI: 10.1016/j.lindif.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

A twin and adoption study of reading achievement: Exploration of shared-environmental and gene–environment-interaction effects

Abstract: Existing behavior-genetic research implicates substantial influence of heredity and modest influence of shared environment on reading achievement and reading disability. Applying DeFries-Fulker analysis to a combined sample of twins and adoptees (N = 4,886, including 266 reading-disabled probands), the present study replicates prior findings of considerable heritability for both reading achievement and reading disability. A simple biometric model adequately described parent and offspring data (combined N = 9,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…We do not know of other studies that have found evidence for non-additive (or dominant) genetic influence on reading (dis)ability (e.g. Kirkpatrick et al, 2011). Reading ability of spouses appeared to be correlated (assortative mating, 0.38), which is in line with findings from Wadsworth et al (2002: 0.26) and other studies of traits that correlate with reading, like intelligence (Vinkhuyzen, van der Sluis, Maes, & Posthuma, 2012: 0.37), but lower than found by van Bergen et al (2015: 0.16).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We do not know of other studies that have found evidence for non-additive (or dominant) genetic influence on reading (dis)ability (e.g. Kirkpatrick et al, 2011). Reading ability of spouses appeared to be correlated (assortative mating, 0.38), which is in line with findings from Wadsworth et al (2002: 0.26) and other studies of traits that correlate with reading, like intelligence (Vinkhuyzen, van der Sluis, Maes, & Posthuma, 2012: 0.37), but lower than found by van Bergen et al (2015: 0.16).…”
Section: Discussionmentioning
confidence: 96%
“…Two English studies tried to disentangle genetic and environmental influences within the family. A study that includes parent and (adoptive) child data (Kirkpatrick, Legrand, Iacono, & Mcgue, 2011) provides a genetically sensitive design. This study employed a broad construct of literacy (Wide Range Achievement Test), but did not explicitly test the nature of familial transmission.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can be extended to the case of a categorical disorder, by converting the concordance for disorder in MZ and DZ twins to tetrachoric correlations [17]. If, however, the disorder is defined in terms of a quantitative dimension, another method, DeFries-Fulker analysis [18], can be used.…”
Section: Methods For Investigating Multifactorial Disordersmentioning
confidence: 99%
“…DeFries-Fulker analysis of reading difficulties has been used with three large samples: from the Colorado Learning Disabilities Research Center (CLDRC) [19], from the Twins Early Development Study [20] and from a large sample of twins and adoptees in Minnesota [17]. In all three studies, the heritability of reading disability was estimated to be at least 60%.…”
Section: Methods For Investigating Multifactorial Disordersmentioning
confidence: 99%
See 1 more Smart Citation